Pengaruh Lingkungan Kerja dan Deskripsi Pekerjaan Terhadap Kinerja Pegawai di Kantor Kecamatan Sungai Pinang Kota Samarinda - Erly Pratiwi; Adam Idris; Mohammad Taufik (Jurnal Ilmu Pemerintahan, 2024)
This research is motivated by phenomena related to the performance of existing government apparatus employees, including the limited ability of employees to carry out their duties, the lack of suitability of educational background and position, and work time discipline. There are several factors that can influence employee performance, one of which is the work environment and job description. The hypothesis proposed and making proof that job environment, job descriptions has an impact on employee performance in Kantor Kecamatan Sungai Pinang Kota Samarinda. The results of this research can be concluded that the Work Environment (X1) and Job Description (X2) together (simultaneously) prossess a totable impact on Employee (Y). An Rsquare is 74,2% indicates that the work employee description have significant impact on employee performance. With the remaining 25.8% being impact of other variables not looked at in this examination.